Transforaminal Epidural Steroid Injection in the Treatment of_x000D_ Pain in Foraminal and Paramedian Lumbar Disc Herniations - (:unkn) unknown (My University, 2019)
AIM: To compare the effect of fluoroscopically guided transforaminal epidural steroid injections on radicular pain in foraminal andparamedian lumbar disc herniations.MATERIAL and METHODS: This study included patients who did not benefit from previous medical treatments or are not suitablefor surgery. Transforaminal epidural steroid injections for the treatment of foraminal and paramedian lumbar disc herniationwere performed in 370 and 1262 patients, respectively. Every group’s preprocedural visual analogue scale (VAS) and 12-weekpostprocedural VAS scores were recorded, and statistical analysis was performed. The complications noted were also recorded.RESULTS: The preprocedural and postprocedural mean VAS scores for radicular pain in foraminal disc herniation were 67.11 ± 4.28and 34.78 ± 3.64, respectively. However, the preprocedural and postprocedural mean VAS scores in paramedian disc herniationwere 62.16 ± 6.65 and 19.07 ± 4.50, respectively. Statistical analysis of the varying preprocedural and postprocedural VAS scoresshowed that transforaminal epidural steroid injections were more effective for paramedian disc herniation than for foraminal discherniation (p<0.05).CONCLUSION: Transforaminal epidural steroid injections were more effective for paramedian lumbar disc herniation than forforaminal disc herniation, 12 weeks after the procedure.